1999
DOI: 10.1002/(sici)1097-0290(19990205)62:3<336::aid-bit10>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects on recombinant interferon-? glycosylation in continuous culture of Chinese hamster ovary cells

Abstract: Asparagine linked (N‐linked) glycosylation is an important modification of recombinant proteins, because the attached oligosaccharide chains can significantly alter protein properties. Potential glycosylation sites are not always occupied with oligosaccharide, and site occupancy can change with the culture environment. To investigate the relationship between metabolism and glycosylation site occupancy, we studied the glycosylation of recombinant human interferon‐γ (IFN‐γ) produced in continuous culture of Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 56 publications
2
72
0
Order By: Relevance
“…While the limitation of glucose in the culture medium allows to reduce lactate production 77 , it has been observed that critical limitation of the former leads to glycosylation heterogeneity 78 , due to a decreased UDP-acetylglucosamine (UDP-GlcNAc) availability 79 . The absence of glucose affects the synthesis of oligosaccharide precursors, as glucose-starved cells alter its synthesis process 80 .…”
Section: Non Specific Impact Of Media Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the limitation of glucose in the culture medium allows to reduce lactate production 77 , it has been observed that critical limitation of the former leads to glycosylation heterogeneity 78 , due to a decreased UDP-acetylglucosamine (UDP-GlcNAc) availability 79 . The absence of glucose affects the synthesis of oligosaccharide precursors, as glucose-starved cells alter its synthesis process 80 .…”
Section: Non Specific Impact Of Media Componentsmentioning
confidence: 99%
“…Metabolomic analysis of fed-batch cultures revealed increasing ornithine levels coincided with higher high mannose glycan levels 285 . In continuous CHO cell culture producing interferon-γ, site glycosylation occupancy was linked with the intracellular UDP-N-acetylgalactosamine concentration 79 . Ammonium plays an active part in the regulation of the pH of acidic intracellular compartments of CHO expressing recombinant immunoadhesin tumor necrosis factor-IgG (TNFR-IgG), including trans-Golgi and it affects intracellular nucleotide sugar pools, especially UDP-N-acetylglucosamine (UDP-GlcNAc) and UDP-N-acetylgalactosamine 237 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been reported in characterization of growth and metabolism over a wide range of dilution rates for CHO cells (Heidemann et al, 1998;Nyberg et al, 1999), hybridoma cells (Frame and Hu, 1991;Ray et al, 1989;Vriezen and van Dijken, 1998) and BHK cells (Carrondo et al, 1999;Hu et al, 2000).…”
Section: Continuous Culturementioning
confidence: 99%
“…This result may be explained by a high level of peptides consumed by infected Sf9 cells in Sf900™III at the low ICD. There is evidence that very small peptides contribute to the nutritional value of a medium as a source of AAs (Heidemann et al, 2000;Nyberg et al, 1999) and so it is possible that the use of small oligo-peptides as an AA source is preferable than the use of free AAs in some situations. Di-peptides and tri-peptides are taken up more readily in the intestine than corresponding free amino acids (Grimble et al, 1987;Silk et al, 1985).…”
Section: Low Intracellular Aa Concentrations At High Icds In Comparismentioning
confidence: 99%